The Impact of Body Mass Index on Osteoarthritis Severity Levels - Siti Juhro; Much Nurkharistna Al Jihad; Machmudah Machmudah; Dera Alfiyanti (Media Keperawatan Indonesia)
Osteoarthritis (OA) is a degenerative joint disease characterized by cartilage damage, with pain being one of the most frequent complaints among patients. Globally, approximately 151.4 million people suffer from OA, including 27.4 million in Southeast Asia, making it a leading cause of disability among adults. Body Mass Index (BMI) is a significant risk factor influencing the development and severity of OA. This study aimed to analyze the relationship between BMI and osteoarthritis severity. A descriptive cross-sectional design was employed, with data collected from medical records of 106 osteoarthritis patients, selected through total sampling. Data were analyzed using the Kolmogorov-Smirnov test for normality, followed by the Pearson correlation test for normally distributed data. The analysis revealed a significant relationship between BMI and the degree of osteoarthritis (p = 0.001, r = 0.308), indicating a low-strength correlation. These findings suggest that higher BMI is associated with increased severity of osteoarthritis. Further research and targeted interventions are recommended to manage BMI as part of osteoarthritis prevention and treatment strategies.